2012
DOI: 10.1007/s00776-011-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire (JHEQ): a patient-based evaluation tool for hip-joint disease. The Subcommittee on Hip Disease Evaluation of the Clinical Outcome Committee of the Japanese Orthopaedic Association

Abstract: BackgroundThe Japanese Orthopaedic Association Hip Score is widely used in Japan, but this tool is designed to reflect the viewpoint of health-care providers rather than that of patients. In gauging the effect of medical therapies in addition to clinical results, it is necessary to assess quality of life (QOL) from the viewpoint of patients. However, there is no tool evaluating QOL for Japanese patients with hip-joint disease.MethodsWith the aim of more accurately classifying QOL for Japanese patients with hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 16 publications
0
66
0
Order By: Relevance
“…The JHEQ is a PRO tool first reported in 2012 by Matsumoto et al [5] for evaluation of the hip joint. This self-administered questionnaire uses a five-point Likert scale and comprises 24 questions in three scales (pain on a visual analog scale, movement, and mental; 8 questions in each subscale).…”
Section: Jheqmentioning
confidence: 99%
See 2 more Smart Citations
“…The JHEQ is a PRO tool first reported in 2012 by Matsumoto et al [5] for evaluation of the hip joint. This self-administered questionnaire uses a five-point Likert scale and comprises 24 questions in three scales (pain on a visual analog scale, movement, and mental; 8 questions in each subscale).…”
Section: Jheqmentioning
confidence: 99%
“…Among postoperative evaluation methods for THA, clinician-reported outcomes (CROs) such as the Harris Hip Score are affected by biases including intraobserver and interobserver variability and differences in patients' understanding of the questions asked [5]. Therefore, patient-reported outcomes (PROs) have attracted attention for more accurate evaluation of patients' quality of life.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Matsumoto et al 13 reported Cronbach a coefficients of 0.95, 0.93, and 0.93 for the pain, movement, and mental subscales, respectively. Similarly, Seki et al 14 reported Cronbach a coefficients of 0.92, 0.91, and 0.94 for each subscale.…”
Section: S34mentioning
confidence: 99%
“…11,12 The recently developed Japanese Orthopaedic Association Hip-Disease Evaluation Questionnaire (JHEQ) includes questions related to common Asian-lifestyle movements, such as using a squatting pan toilet or getting up from the floor. Matsumoto et al 13 suggested…”
Section: Introductionmentioning
confidence: 99%